At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Solve the following system of equations:

[tex]\[
\begin{array}{l}
\frac{x}{2} + y = 0.8 \\
\frac{7}{x + \frac{y}{2}} = 10
\end{array}
\][/tex]


Sagot :

Sure, let's solve the given system of equations step-by-step. The system of equations is:

[tex]\[ \begin{array}{l} \frac{x}{2} + y = 0.8 \quad \text{(Equation 1)}\\ \frac{7}{x + \frac{y}{2}} = 10 \quad \text{(Equation 2)} \end{array} \][/tex]

Step 1: Solve the first equation for [tex]\( y \)[/tex].

Starting with Equation 1:

[tex]\[ \frac{x}{2} + y = 0.8 \][/tex]

Subtract [tex]\(\frac{x}{2}\)[/tex] from both sides:

[tex]\[ y = 0.8 - \frac{x}{2} \][/tex]

Step 2: Substitute the expression for [tex]\( y \)[/tex] into the second equation.

Using [tex]\( y = 0.8 - \frac{x}{2} \)[/tex] in Equation 2:

[tex]\[ \frac{7}{x + \frac{0.8 - \frac{x}{2}}{2}} = 10 \][/tex]

Simplify the denominator of the fraction:

[tex]\[ \frac{7}{x + \frac{0.8}{2} - \frac{x}{4}} = 10 \][/tex]

[tex]\[ \frac{7}{x + 0.4 - \frac{x}{4}} = 10 \][/tex]

Combine like terms in the denominator:

[tex]\[ \frac{7}{x - \frac{x}{4} + 0.4} = 10 \][/tex]

Simplify the terms involving [tex]\( x \)[/tex]:

[tex]\[ \frac{7}{\frac{4x - x}{4} + 0.4} = 10 \][/tex]

[tex]\[ \frac{7}{\frac{3x}{4} + 0.4} = 10 \][/tex]

Step 3: Solve for [tex]\( x \)[/tex].

To clear the fraction in the denominator, multiply both sides by [tex]\(\frac{3x}{4} + 0.4\)[/tex]:

[tex]\[ 7 = 10 \left( \frac{3x}{4} + 0.4 \right) \][/tex]

Distribute the 10:

[tex]\[ 7 = \frac{30x}{4} + 4 \][/tex]

Simplify the fraction:

[tex]\[ 7 = \frac{15x}{2} + 4 \][/tex]

Subtract 4 from both sides:

[tex]\[ 3 = \frac{15x}{2} \][/tex]

Multiply both sides by [tex]\(\frac{2}{15}\)[/tex]:

[tex]\[ x = \frac{3 \cdot 2}{15} = \frac{6}{15} = \frac{2}{5} = 0.4 \][/tex]

So, [tex]\( x = 0.4 \)[/tex].

Step 4: Substitute [tex]\( x \)[/tex] back into the expression for [tex]\( y \)[/tex].

Using [tex]\( x = 0.4 \)[/tex] in [tex]\( y = 0.8 - \frac{x}{2} \)[/tex]:

[tex]\[ y = 0.8 - \frac{0.4}{2} \][/tex]

[tex]\[ y = 0.8 - 0.2 \][/tex]

[tex]\[ y = 0.6 \][/tex]

Therefore, the solution to the system of equations is:

[tex]\[ x = 0.4 \quad \text{and} \quad y = 0.6 \][/tex]